2011
DOI: 10.1200/jco.2010.32.2107
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Single-Agent Arsenic Trioxide for the Front-Line Therapy of Acute Promyelocytic Leukemia

Abstract: Purpose The long-term follow-up results of patients with acute promyelocytic leukemia (APL) treated with all-trans retinoic acid and chemotherapy show high cure rates. Several studies have shown high efficacy of single-agent arsenic trioxide in newly diagnosed APL. However, long-term follow-up results are needed. Patients and Methods One hundred ninety-seven patients with newly diagnosed APL were treated with arsenic trioxide 0.15 mg/kg daily intravenous infusion until complete remission (CR). After achieving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
138
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(141 citation statements)
references
References 21 publications
1
138
0
1
Order By: Relevance
“…ED, the term proposed 20 years ago when ATRA had not been widely used, 94 has recently attracted attention again from investigators. 33,95,96 Park et al 97 reported 1400 cases of APL from 1992 to 2007, the overall ED rate was 17.3%, and only a modest change in ED was observed over time. Lehmann et al 98 reported 105 cases of APL patients among whom the frequency of ED (within 30 days) actually reached 29%, a rate significantly higher than those in non-APL AML, especially evident in the elderly (460 years) population.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…ED, the term proposed 20 years ago when ATRA had not been widely used, 94 has recently attracted attention again from investigators. 33,95,96 Park et al 97 reported 1400 cases of APL from 1992 to 2007, the overall ED rate was 17.3%, and only a modest change in ED was observed over time. Lehmann et al 98 reported 105 cases of APL patients among whom the frequency of ED (within 30 days) actually reached 29%, a rate significantly higher than those in non-APL AML, especially evident in the elderly (460 years) population.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Despite being a frequently used anticancer agent in APL, ATO may also induce unwanted or fatal side effects, including differentiation syndrome, QT interval prolongation, hepatotoxicity, the incidence of secondary malignancies and damage to the nervous system (38,39). In the present study, CQ functioned synergistically with ATO, indicating that a lower dose of ATO is required to achieve the same curative effect when combined with CQ, therefore reducing the risks associated with ATO.…”
Section: Discussionmentioning
confidence: 61%
“…Our results are comparable to in the study by Mathews et al [4] where median time for hematological CR 43 days. But in the study by Ghavamzadeh et al [10] the median duration was only 30 days. In our study hydroxyurea was used to reduce the count for a mean duration of 15.82 days.…”
Section: Discussionmentioning
confidence: 97%
“…We encountered differentiation syndrome in 2 patients and both of them were treated with dexamethasone. In the study by Ghavamzadeh et al [10] 13.2 % of induction death was due to differentiation syndrome [10]. There was no grade 3 or 4 neutropenia/ hepatotoxicity encountered.…”
Section: Discussionmentioning
confidence: 99%